Critical factors influencing visitor emotions: analysis of “restorativeness” in urban park visits in Fuzhou, China - Wu, Yu; Liu, Jian; Quevedo, Jay Mar D.; Cheng, Huishan; Yu, Kunyong; Kohsaka, Ryo (Frontiers in Public Health, 2023)
To date, a comprehensive analysis of urban green space (UGS) visitors' emotional remains largely unexplored. In this study, we focus on how UGS environmental preferences, restorativeness, other physical factors (sound, air, and thermal environments), and individual characteristics affecting visitor emotions. Such a comprehensive analysis would allow relevant practitioners to check the environmental quality of UGSs and improve certain conditions to promote visitor emotions. A total of 904 questionnaire responses with concurrently monitored physical factors were analyzed by independent sample t-tests, one-way ANOVA and path analysis. The results indicate that the influence of different UGS environmental factors on visitors' emotions vary, as does their impacts on positive versus negative emotions. Positive emotions were generally more affected than negative emotions by UGS. Visitor emotions were mainly influenced by physical and psychological factors. Specifically, the thermal evaluation had the largest impact on positive emotions (β = 0.474), followed by perceived restorativeness (β = 0.297), which had β values of -0.120 and -0.158, respectively, on negative emotions. Air evaluation was more effective for increasing positive emotions (β = 0.293) than reducing negative emotions (β = -0.115). Sound evaluation also had similar results (β = 0.330 vs. β = -0.080). Environmental preference significantly influenced only positive emotions (β = 0.181) but could still indirectly impact negative emotions. Moreover, objective physical factors can indirectly affect visitors' emotions by enhancing their evaluations. Thus, a broad range of factors, including air quality, sound, thermal, and restorative environments, and environmental preferences, should be considered. Corresponding suggestions are proposed for UGS design and management in this study.